Relationships of morphological groups in the northern flicker superspecies complex (Colaptes auratus & C. chrysoides). Issue 3 (4th May 2017) - Manthey, Joseph D.; Geiger, Mark; Moyle, Robert G.
Abstract : Many species complexes have diversified rapidly and recently, resulting in morphologically diverse populations; however, the rapid pace of diversification often prevents identification of clear phylogeographic structure. Recently, the use of large genomic and reduced-representation genomic datasets has improved resolution of the evolutionary histories in such species and allowed identification of lineages on distinct evolutionary trajectories. The northern flicker ( Colaptes auratus ) and gilded flicker ( Colaptes chrysoides ) form a polytypic superspecies group with a complex taxonomic history. The superspecies group includes up to 13 described subspecies, which represent slight geographic variation among five main morphological groups: red-shafted flickers of western North America ( cafer group), yellow-shafted flickers of eastern North America ( auratus group), Cuban flickers of the Caribbean ( chrysocaulosus group), gilded flickers of the U.S. south-west and Mexican north-west ( chrysoides group), and Guatemalan flickers of Central America ( mexicanoides group). These groups are largely differentiable by variation in feather shaft colour, malar colour, throat colour, crown colour, and back barring. Here, using mitochondrial DNA (mtDNA) and hundreds of single nucleotide polymorphisms (SNPs), we characterized the genetic relationships and genomic distinctiveness of the five morphological groups. We found the mexicanoides group to be the most genetically distinct in both mtDNA (∼1.4% sequence divergence) and large SNP panels. The chrysocaulosus group is differentiated by a single basepair mutation in a small mtDNA fragment. In both mtDNA and SNP panels, there is little genetic distinctiveness between auratus, cafer, and chrysoides morphological groups, with evidence of admixture and a lack of fixed differences.